The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0103-84782009000800016
|View full text |Cite
|
Sign up to set email alerts
|

Pré-resfriamento em água de lichia 'B3' mantida em armazenamento refrigerado

Abstract: RESUMO Este experimento visou a estudar o efeito de diferentes temperaturas e tempos de pré-resfriamento em água sobre a qualidade de lichias 'B3', após a frigoconservação. Os tratamentos foram: T1 = controle (sem pré

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
0
3
0
8
Order By: Relevance
“…Lightness (L) of ripe fruits of each lychee variety according to fruit thinning intensity. Aguila et al (2009) evaluated cooling in water for "Kwai May Pink" lychee fruits prior to cold storage; they verified that fruit from control presented an L value of 37, reducing to 34 after 7 days of storage. Lima et al (2011) reported that 'Bengal' variety fruit showed an L value of 39.5 at room temperature, being higher than was that found here (35.65), but similar to that of 'Mauritius' variety.…”
Section: Pericarp Colormentioning
confidence: 94%
“…Lightness (L) of ripe fruits of each lychee variety according to fruit thinning intensity. Aguila et al (2009) evaluated cooling in water for "Kwai May Pink" lychee fruits prior to cold storage; they verified that fruit from control presented an L value of 37, reducing to 34 after 7 days of storage. Lima et al (2011) reported that 'Bengal' variety fruit showed an L value of 39.5 at room temperature, being higher than was that found here (35.65), but similar to that of 'Mauritius' variety.…”
Section: Pericarp Colormentioning
confidence: 94%
“…O armazenamento refrigerado e o pré-resfriamento são algumas dessas técnicas, podendo ser utilizados de forma isolada ou combinados. Quando utilizados corretamente, são eficientes e práticos na conservação pós-colheita de frutos in natura (DEL AGUILA et al, 2009;SENHOR et al, 2009).…”
Section: Introductionunclassified
“…pertence à família Sapindaceae e é originária da parte subtropical da China. Seu alto potencial comercial é devido ao seu sabor levemente acidificado, excelente aroma, elevado valor nutritivo e cor vermelha brilhante da casca (AGUILA et al, 2009).…”
Section: Introductionunclassified
“…Entretanto, após a colheita, os frutos apresentam rápido escurecimento e perda da coloração vermelha da casca, o que limita sua comercialização (AGUILA et al, 2009;HOJO et al, 2011). O escurecimento pós-colheita é resultado de um processo geralmente atribuído à degradação dos pigmentos vermelhos (antocianinas), associado com a oxidação de compostos fenólicos pelas enzimas polifenoloxidase (PPO) e/ou peroxidase (POD) (SOUZA et al, 2011).…”
Section: Introductionunclassified